Heading West : Oregon Trail and westward expansion - Loh-Hagan, Virginia (Loh-Hagan, Virginia. Behind the curtain., 2019)
Presents a short play for seven students to act out depicting the life and struggles of American pioneers moving west to new lands on the Oregon Trail. Includes background information on this time period, a timeline, and a brief history of several real historical settlers, like those of the Donner Party.